A Study on user comfort satisfaction establishing a guideline for technical vocational education and training (TVET) centers for the tourism sector in Davao City - Ong, Aleah Grace A.; Ylagan, Myrafe S. (2023)
This thesis presents a comprehensive study conducted to explore and establish guidelines for enhancing user comfort satisfaction in Technical Vocational Education and Training (TVET) centers within the tourism sector in Davao City. The study was conducted at the three TVET centers namely: the RTC-DavKor; ATVI; and the SACT. The research aimed to investigate whether the key factors for comfort & satisfaction under the three main themes: Human themes, Building & Site themes, and Indoor Space themes are met within the existing training centers. This study employed a descriptive-quantitative approach, combining multiple methods such as photo documentation and observation, survey questionnaires, and key informant questionnaires. The data gathered were analyzed using the SWOT Analysis, IBM SPSS Statistics, Garrett Ranking Method, and Thematic Analysis.The findings revealed that the students of the three training centers have a high satisfactory level on the three themes. However, an evaluation of the workstations in the three training centers revealed that the existing conditions does not meet the design standards necessary for optimal comfort. The findings also revealed the four (4) main factors: Spatial perception; Physical environment; Teaching interaction; & Learning support; that were found to be significant in contributing to user comfort satisfaction. The findings of the study served as a foundation for the development of guidelines aimed at improving comfort levels within the training centers. Implementing these guidelines will contribute to creating an optimal learning environment that enhances user comfort satisfaction and ultimately improves the overall training experience for students.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023